The effect addition of epigallocatechin-3-gallate (EGCG) in nano hydroxyapatite on surface porosity as a candidate pulp capping materia - Ismiyatin, Kun; Zubaidah, Nanik; Azzaria, Indira Moza (Universitas Airlangga, 2023)
Background: Deep caries, cavity preparation and use of burs or other dental instruments often result in pulpal perforation. In the case of an exposed pulp, regenerative pulp tissue treatment aims to regenerate normal tissue and maintain pulp vitality by inducing pulp regeneration using the right material, so that a good percentage and size of material porosity is needed to help cell regeneration by supporting cell proliferation and attachment, stimulating remineralization and differentiation of odontoblast-like cells. Nano-HA has the ability to produce dentine bridges continuously, has porous properties that allow cell growth, improves mechanical properties, but is not anti-inflammatory so that EGCG is added which has the advantage of being an antioxidant, anti-inflammatory which can optimize pulp tissue regeneration and also acts as an antimicrobial by reduce the growth of bacteria in the oral cavity and can trigger the proliferation and differentiation of human dental pulp cells. Purpose: This study aims to prove the difference in surface porosity of nano hydroxyapatite added with EGCG compared to nano hydroxyapatite and aquadest. Methods: This study used a laboratory experimental study with a posttest-only control group design. The research sample consisted of 32 samples which were divided into 2 groups, the treatment group (nano HA - EGCG) and the control group (nano HA - aquadest). Each research group was subjected to freeze drying and SEM tests. Results: There was a significant difference in the percentage of surface porosity between the nano hydroxyapatite added with EGCG compared to nano hydroxyapatite and aquadest.on the results of the Independent T-test (p<0.05). Conclusion: The addition of EGCG to nano hydroxyapatite has a higher porosity percentage compared to nano hydroxyapatite with aquadest.